Beneficial Potential of Banha-Sasim-Tang for Stress-Sensitive Functional Dyspepsia via Modulation of Ghrelin: A Randomized Controlled Trial - Kim, Sul-Ki; Joung, Jin-Yong; Ahn, Yo-Chan; Jung, In-Chul; Son, Chang-Gue (Frontiers in Pharmacology, 2021)
Background: Functional dyspepsia (FD) is a highly complex pathophysiologic disease, which shows low recovery and high relapse rates. Therefore, a growing number of clinicians and patients are looking for alternative herbal medicine. Banha-Sasim-Tang (BST) is an herbal prescription for treating a wide range of dyspepsia in traditional Korean medicine (TKM). Aim of the study: This study aimed to evaluate the efficacy of BST on FD in patients with psychological stress-related symptoms and to investigate the involvement of ghrelin. This study is registered at https://cris.nih.go.kr/with the identification number KCT 0002811. Materials and methods: A total of 31 participants with FD who met the Rome IV criteria and the psychological stress-related pattern were enrolled in a double-blind, randomized, and controlled study. Participants were randomly assigned to the BST group (10 g twice daily for 4 weeks) or placebo group. The primary endpoint was a change in the Nepean Dyspepsia Index–Korean (NDI-K) score. The secondary endpoints were changes in the Visual Analog Scale (VAS) scores and plasma ghrelin level. Results: All participants completed the study (n = 15 for BST, n = 16 for placebo). BST decreased NDI-K scores compared with placebo, but the difference was not statistically significant (37.40 ± 27.40 vs 22.50 ± 23.85, p = 0.12). VAS scores and plasma total ghrelin levels were significantly improved in patients who were treated with BST (3.19 ± 1.60 vs 1.38 ± 2.85, p = 0.03 for VAS and 105.69 ± 287.89 vs -142.31 ± 314.32, p = 0.03 for total ghrelin). No BST-related adverse effects were observed during the trial. Conclusion: Our results indicate the clinical potential of BST for FD patients and are the first study to show the modulation of plasma ghrelin as one of its corresponding mechanisms. Clinical Trial Registration:https://cris.nih.go.kr/, identifier KCT 0002811.